Risk factors for mixed chimerism in children with hemophagocytic lymphohistiocytosis after reduced toxicity conditioning. Issue 9 (3rd July 2020) - Wustrau, Katharina; Greil, Johann; Sykora, Karl‐Walter; Albert, Michael H.; Burkhardt, Birgit; Lang, Peter; Meisel, Roland; Wössmann, Wilhelm; Beier, Rita; Schulz, Ansgar; Bader, Peter; Chada, Martin; et al.
Abstract: Background: Reduced toxicity conditioning for hematopoietic stem cell transplantation of patients with hemophagocyticlymphohistiocytosis (HLH) results in favorable survival, however at the expense of relevant rates of mixed chimerism. Factors predisposing to mixed chimerism remain to be determined. Procedure: Patients with primary HLH transplanted 2009‐2016 after treosulfan‐ or melphalan‐based conditioning regimens were analyzed in a retrospective multicenter study for survival, engraftment, chimerism, and adverse events. Mixed chimerism was considered substantial if < 25% donor chimerism occurred and/or if secondary cell therapy was administered. Donor type, graft source, type of alkylating agent, type of serotherapy, and remission status were analyzed as potential risk factors in a multivariable logistic regression model. Results: Among 60 patients, engraftment was achieved in 95%, and the five‐year estimated overall survival rate was 75%. Prevalence of any recipient chimerism was 48%. Substantial recipient chimerism was recorded in 32% of patients. Secondary post‐HSCT cell therapy was administered in 30% of patients. A human leukocyte antigen (HLA)‐mismatched donor (< 10/10) was the only significant risk factor for the occurrence of substantial recipient chimerism ( P = 0.01; odds ratio, 5.8; CI 95%, 1.5‐26.3). Conclusion: The use of an HLA‐matched donor is the most important factor to avoid substantial recipient chimerism following treosulfan ‐or melphalan‐based conditioning in primary HLH.